Soil Biota Build-up under Organic and Inorganic Fertilization in Semi-arid Central India - Roy, S; Saxena, P; Bano, R (Annals of Arid Zone, 2016)
study was conducted in semi-arid central India, to investigate the response of organic and inorganic nutrient sources on soil biota in an intensive forage production system (cowpea intercropped with maize in rainy season followed by lucerne in winter). Field treatments included unfertilized control, NPK at recommended doses and FYM as per the recommended N requirement of crops. Both the inorganic and organic nutrients had increased the population of various soil biota. But change in abundance from initial was significant under organic nutrient source (collembolan = 26.0%, oribatida mites = 8.3%, other mites = 8.1%, nematodes = 2.4%, actinomycetyes = 3.9%, bacteria = -14.0% and fungi = 6.9%). Green fodder yield (GFY) was significantly higher under the organic plots (35.78 t ha-1) compared to the inorganic fertilizer (31.64 t ha-1). This positive impact of manure on GFY was realized in both drought and erratic rain years. Compared to unfertilized control, application of manure increased soil moisture, soil organic carbon and nitrogen (8.85%, 56%, 65%, respectively). Available nitrogen (22%), available potassium (83%) and available phosphorus (40%) had also increased in plots receiving organic nutrient source. Therefore, we conclude that application of manure will improve quality and biological activity of the nutrient deficit Alfisol. Key words: Forage production system, FYM, micro-flora, micro-arthropods, nematodes, NPK.